The Concept and a Legal Nature of the Prosecutor’s Supervision - Липівський, В.В (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
The paper discusses main ideas in formation of the concept of prosecutor’s supervision in criminal process of Ukraine through understanding it’s subject, object, main tasks, objective and specifcs. In the article describes few scientist’s opinions of supervision’s place in prosecutor’s function system and the author made his own. Moreover the author made correlation between terms «prosecutor’s supervision» and «procedure guidance», describes other scientists opinion. Likewise, the author consider, that terms «control» and «supervision» have the same tasks and similar nature, but difer in subject of it’s application. In addition, paper analyses new constitutional states which regulate prosecutor’s activities and function in criminal process of Ukraine. Furthermore, new constitutional states create legal collision with states of the law of Ukraine «About prosecutor’s ofce». Consequently, the author insist on change of the legislation to minimize legal collision and possible problems in practice in future.Finally, the author shows that partition on supervision and guidance functions is factitious, because both of this categories have universal character and closely linked among themselves. The paper shows, that providing new statement about «procedure guidance» doesn’t creates a new function of prosecution, but only gives general name of the constitutional form and reason of its providing is implementation of prosecution changelessness principle.It is concluded that procedure guidance is a form of a prosecutorial supervision as the constitutional function.

У статті автором досліджено поняття прокурорського нагляду, його предмет, об`єкт, завдання, висвітлено співвідношення прокурорського нагляду та процесуального керівництва. Зроблено висновок про те, що процесуальне керівництво є формою реалізації конституційної функції нагляду.
ПОНЯТТЯ ТА ПРАВОВА ПРИРОДА ПРОКУРОРСЬКОГО НАГЛЯДУ
Keywords: Prosecutor’s Ofce of Ukraine; procedural guidance; prosecutor’s power; pretrial investigation; прокуратура України; прокурорський нагляд; процесуальне керівництво; кримінальне провадження